Implementation of the Merdeka Curriculum in Islamic Religious Education at Bandar Lampung State High School 1 - Ingtia Juli Wantari; Ahmad Ainur Rofiq; Linda Nur Ainah (Institute of Advanced Knowledge and Science, 2026)
The implementation of the Independent Curriculum has brought about changes in the learning system, making it more flexible and student-centered. Islamic Religious Education plays a crucial role in shaping students' religious character. This study aims to describe the implementation of the Independent Curriculum in Islamic Religious Education learning, encompassing planning, implementation, and assessment. This study used a descriptive qualitative approach. The results show that the implementation of the Independent Curriculum in Islamic Religious Education learning is carried out through the development of teaching modules, project-based learning, contextual learning, and authentic assessment. This implementation has resulted in increased student engagement, religious attitudes, and social skills. Thus, the Independent Curriculum is able to improve the quality of Islamic Religious Education learning in a more meaningful and student-centered manner. Keywords : Independent Curriculum, Islamic Religious Education